Preface - Designing or Choosing Languages for Teaching Programming - Juraj Hromkovič; Dennis Komm (Informatics in Education)
Niklaus Wirth, one of the most influential pioneers of computer science, passed away in Zurich on January 1st of this year. His contributions to software engineering and especially to programming languages are fundamental, unique, and simply amazing. And they have had a huge impact on computer science education worldwide. His concept of simplicity and transparency has changed the style of programming and moved technical coding to enjoyable, creative work. This opened a new dimension in education. Learning by creative work, developing one’s own products, and then starting to investigate their functionality and properties in order to work on their improvements in a never-ending loop. With this special issue we are thanking Niklaus Wirth for his pioneering work in the development of programming languages and in informatics education, and saluting his life’s work.